Free to Move: Migration, Tax Competition and Redistribution - Woojin Lee (University of Massachusetts, Department of Economics, 2005)
We study a model of tax competition between two countries when both skilled and unskilled workers make their migration decisions simultaneously and wages are endogenously determined. If both factors of production are allowed to migrate freely and when the demand for skilled labor is not so elastic, the problem typically predicted in the literature of tax competition that increased mobility of production factors will pose a severe threat to redistribution possibility is less acute than it might first appear. The equilibrium tax rate can be not only positive but also increasing in the degree of mobility of unskilled workers. This is mainly because an initial change in migration flows induced by an increase in the tax rate brings about a higher wage for skilled workers and a lower wage for unskilled workers, which offsets the initial adverse effect. We also show that in contrast to the conventional wisdom in the literature of tax competition decreasing the tax rate invites not only skilled workers but also unskilled workers; unskilled workers always chase skilled workers at the equilibrium. JEL Categories: D50, F21, H30
Keywords: 330; globalization; mobility; tax competition; redistribution; fiscal externality; political economy